The psychological and immunobiological implications of COVID-19: The possible correlation with previous pandemics and the suggestive therapeutic hypothesis of convalescent plasma - Giulio Perrotta (Global Journal of Clinical Virology - Peertechz Publications, 2021)
ious pandemics.  Methods: The selected population sample was 765 total Italian Covid positive symptomatic and asymptomatic patients, divided into the two categories (308 symptomatic and 457 asymptomatic) and by age groups. In order to investigate these elements, an information questionnaire was specifically drawn up concerning the state of health and the period of the illness, in addition to the personal and family history and the specific indicators identified for this research.  Results: The first level concerns the psychological implication during and after the viral infection, whereby: a) symptomatic individuals with a previous psychological diagnosis (127 patients) reported medium-high values of malaise in all three areas of investigation for 51.02% (65 patients), with the high value of malaise for 48.98% (62 patients) and a consequent worsening of the previous psychopathological condition, especially for those who declared to suffer from mood, anxiety, obsessive and somatic disorders, persisting even until the sixth month after recovery; b) symptomatic individuals without a previous psychological diagnosis (330 patients) reported medium to high levels of malaise in all three surveyed areas for 72.30% (241 patients), with the highest level of malaise for 27.70% (89 patients) with symptoms typical of mood, anxiety, obsessive and somatic disorders, which persisted even until the sixth month after recovery; c) the asymptomatic patients with a previous psychological diagnosis (87 patients) reported medium-high levels of malaise in all three surveyed areas for 71.25% (62 patients), with the highest level of malaise for 28.75% (25 patients) and a consequent worsening of the previous psychopathological condition, especially for those who declared to suffer from mood, anxiety, obsessive and somatic disorders, lasting up to the sixth month after recovery; d) the asymptomatic patients without a previous psychological diagnosis (221 patients) reported medium-high values of malaise in all three areas of investigation for 90.55% (200 patients), with the highest value of malaise for 9.45% (21 patients) with symptoms typical of mood, anxiety, obsessive and somatic disorders, lasting even until the sixth month after recovery. The second level concerns the immunobiological implication, starting from the question "did your (biological) parents or grandparents contract one of the listed pandemic influences?": 80.34% (618 patients) confirmed the positive answer to the question, while the remaining 16.12% (124 patients) answered "don't know" and 3.54% (23 patients) answered "no".  Conclusions: Despite the limitations of this research, the data obtained make us reflect both on the hypothesis of increasing psychological support for these patients, in order to cope better with their condition, and on the immunobiological hypothesis as described above, wishing for greater attention in the future on these profiles, which are currently underestimated and overshadowed by economic and political interests on the commodification of vaccines by pharmaceutical companies.